Exploring Learners' Learning Styles Preferences: Finding Out the Best Way to Teach ESP - Saptin Dwi Setyo Hastuti (STKIP PGRI SIDOARJO, 2022)
One important key to successful English for Specific Purposes (ESP) is through managing the classrooms. Identifying learners’ learning style preferences can assist teachers in creating a learning environment that is appropriate for the learners. The aim of this study is to explore learners’ learning styles and their impacts on the teaching of ESP. This study involved 284 learners from three different departments, i.e., the tour and travel business department, the tourism department, and the tourism department. The data was collected by using Reid’s Perceptual Learning Styles Preferences Questionnaire (PLSQ). This questionnaire divided learning styles into 4 categories, i.e., auditory, kinaesthetic, visual, and tactile learning styles. It also divided the learning styles into two, i.e., group and individual. This study revealed that most learners were auditory and kinaesthetic learners. Only a few learners were visual and tactile learners. This study also reveals that most learners preferred to work in groups rather than work individually. Considering these findings, learners must participate in determining the activities and environment for teaching a learning process to avoid mismatching between learners’ learning styles and teaching-learning methods. This study offers six recommendations that can be used as a guideline when conducting ESP in the various learning styles preferences.